Rancang Bangun Sistem Aplikasi Kasir Pintar Enterprise Resource Planning (ERP) Berbasis Odoo pada UMKM Rumah Makan Tradisional Uni Mita Lintau - Nendi; Saputra, Hendra Ekky; Suprianto, Ahmad; Aprilia, Putri Dwi; Lestari, Syntha Agung (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The application of information technology on a Micro, Small, and Medium Enterprises (MSME) scale is crucial in increasing competitiveness and operational efficiency in various industrial sectors. In the food and beverage industry, the implementation of a smart cashier application system based on Enterprise Resource Planning (ERP) using the Odoo platform has become a significant concern. This research aims to design and build an ERP-based smart cashier application system using Odoo at the MSME Uni Mita Lintau Traditional Restaurant. By combining Odoo technology with MSME business practices, this research provides a solution to improve operational efficiency and customer experience in traditional restaurants. Through implementation analysis and evaluation, this research offers practical guidance and insight for other MSMEs interested in adopting similar technology to improve their business performance. Thus, this research not only contributes to the practical understanding of the application of technology to MSMEs but also contributes to further developments in the literature on the application of information technology in the food and beverage industry.